Candidate gene discovery in autoimmunity by using extreme phenotypes, next generation sequencing and whole exome capture (2015)
Whole exome sequencing (WES) is a widely used strategy for detection of protein coding and splicing variants associated with inherited diseases. Many studies have shown that the strategy has been broad and proficient due to its ability in detecting a high proportion of disease causing variants, using only a small portion of the genome. In this review we outline the main steps involved in WES, the comprehensive analysis of the massive data obtained including the genomic capture, amplification, sequencing, alignment, curating, filtering and genetic analysis to determine the presence of candidate variants with potential pathogenic/functional effect. Further, we propose that the multiple autoimmune syndrome, an extreme phenotype of autoimmune disorders, is a very well suited trait to tackle genomic variants of major effect underpinning the lost of self-tolerance. © 2014 Elsevier B.V.